Pejalan Independen: Sebuah Diskursus Tentang KeharamanTravel Agent Di Kalangan Backpacker - Puspitarini, Diah; Choesin, Ezra M. (UI Scholars Hub, 2017)
This article discusses the discourse of travelling that has developed among backpackers. Backpacker’s travel are always identical with independent travellers. Independent refers to organizing a whole stories of activities in travelling by themselves. They always do it, without requiring help from others, such as travel agents. The presence of travel agents in the world of travel is contrary to the principles upheld by the independent backpacker. The debate begin when other ideologies of travelling are deliver and the separation of activities between them have started blur. This study used qualitative research methods, with indepth interview and participant observation technique.